Development of a Set of Indicators to Evaluate Injury Control Research Centers. (April 2014) - Runyan, Carol; Garrettson, Mariana; Yee, Sue Lin
Background: Few methods have been defined for evaluating the individual and collective impacts of academic research centers. In this project, with input from injury center directors, we systematically defined indicators to assess the progress and contributions of individual Injury Control Research Centers (ICRCs) and, ultimately, to monitor progress of the overall injury center program. Method: We used several methods of deriving a list of recommended priority and supplemental indicators. This included published literature review, telephone interviews with selected federal agency staff, an e-mail survey of injury center directors, an e-mail survey of staff at the Centers for Disease Control and Prevention, a two-stage Delphi process (e-mailed), and an in-person focus group with injury center directors. We derived the final indicators from an analysis of ratings of potential indicators by center directors and CDC staff. We also examined qualitative responses to open-ended items that address conceptual and implementation issues. Results: All currently funded ICRCs participated in at least one part of the process, resulting in a list of 27 primary indicators (some with subcomponents), 31 supplemental indicators, and multiple suggestions for using the indicators. Conclusion: Our results support an approach that combines standardized definitions and quantifiable indicators with qualitative reporting, which allows consideration of center distinctions and priorities. The center directors urged caution in using the indicators, given funding constraints and recognition of unique institutional environments. While focused on injury research centers, we suggest these indicators also may be useful to academic research centers of other types.